Anyelir Waste Bank Program at Medan City on the Aplication in Circular Economy Techniques - Auliani, Restu; Situmorang, Agnes Aldani; Tanjung, Risnawati; Rusli, Mustar (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The circular economy approach has begun to be applied as a model for waste management in Indonesia. This approach is expected to improve environmental quality and increase economic value. The Anyelir Medan waste bank has implemented the application of circular economics in waste management with the concept of saving waste to gold. This study aims to analyze the operational activities of the carnation waste bank in realizing the circular economic model of waste management. The research method is descriptive research with observational research design. Data is processed using mass balance analysis. Through the Anyelir waste bank, savings can be collected into gold savings under the guidance of PT Pegadaian Persero. Waste managed at the Anyelir waste bank is 1640.94 kg per month with an average of 828.42 kg (50.48%) of plastic waste, 704.58 kg of paper (42.94%) and 107.92 metals (6.58%) . The results of the mass balance analysis show that the total reduction efficiency is 97.2% of the total waste that goes into bank waste. As much as 1450.97 kg (88.42%) of the waste was sold to recycling factories, 41 kg (2.5%) were used as recycled crafts and 103 kg (6.28%) were stored in stock. The rest goes to TPA as much as 45.95 kg (2.8%). The Anyelir waste bank does not only focus on economic value, but also tries to increase awareness of the environment, through education to improve the social life of the community and strengthen the economic pillars. The circular economy movement carried out by the Anyelir waste bank has produced processed waste into compost, recycled creations and raw materials for paper and plastic factories.